Towards sustainable consumption in Albania - Anita Gumeni; Ornela Shalari; Pranvera Mulla (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
In recent years, there has been an increasing awareness towards economic, environmental, and social problems of the actual development system. However, sustainable development remains one of the main challenges of actual times. Sustainable consumption plays a significant role in achieving sustainable development goals. Moving towards more sustainable patterns of consumption will reduce environmental damage, adjust social inequalities, and increase economic efficiency. Therefore, it is substantial to investigate the determinants of sustainable consumption behaviour. The aim of this paper is to identify whether the Albanian consumers adopt sustainable consumption behaviour. An empirical analysis is used to identify the main factors that influence sustainable consumption of Albanian consumers. The results have revealed that sustainable consumption in Albania is a niche segment. The main determinants of sustainable consumption behaviour in Albania are: internal factors such as personality characteristic’s, Perceived Consumer Effectiveness, knowledge, and attitudes towards sustainable consumption, and external factors.